Elderly group satisfaction for stomatological services received at Tomas Romay Policlinic - Milagros Isabel Collazo Ramos; Jorge Luis Calero-Ricardo; Ailec Collazo Llorca; Carlos Mauricio García Collazo (Universidad de Ciencias Médicas de La Habana, 2016)
Introduction: Care quality that is provide to the elderly population, is an important and unpostponable issue Objective: To determine the satisfaction of dental services in "Tomas Romay" polyclinic from the opinions of an elderly group. Materials and Methods: Was performed a descriptive, cross-section research, to 216 elderly men and women, belonging to two doctor´s office of the aforementioned polyclinic. The information was collected through a self-administered questionnaire that was analyzed using descriptive statistics methods. From an ethical point of view, patients had a complete freedom to accept or not their participation in the study. Results: Of the polles, 55.6% were women. The most frequent reason of assistance to the consulting room was related with prosthesis service (38.8%). Interviewee stated as major deficiencies, the lack of material resources, lack of personnel and mainly, the lengthy queuing time to be served. Conclusions: Regardless of the unsatisfactoriness identified by polles, most people consider being satisfied with care receive. Keywords: Stomatological services, health needs, dental prosthesis, population aging.